The Musician's Hand: A Clinical Guide - Winspur, Ian; Parry, Christopher Wynn B. (London Martin Dunitz, 1998)
Clinical guide to special considerations necessary for managing treatment of musician patients. For surgeon, doctors, therapists, music teachers and musicians. High-quality halftone illustrations, photographs, and images.
Keywords: Medicine; Musician; Performance